Unlocking the Health Benefits of Browntop Millet: Antioxidant and Anticancer Activity of Phenolic Extracts - Choudhury, Saddique; Lakshmana, Megha Mallapura; Sihag, Sunil; Kumar, Jayanthi Mallappa (Asian Journal of Biological and Life Sciences, 2025)
Background: Browntop Millet (BTM) bran and seed extracts were evaluated for phenolic distribution, antioxidant (DPPH, FRAP) and anticancer (SRB assay on MDA-MB-231) activities. Results: Bound phenolic-husk extract showed highest antioxidant; bound phenolic-rice extract showed strongest antiproliferative effect. Conclusion: BTM is a potential natural source of antioxidants and antiproliferative agents.
Keywords: Browntop millet; Antioxidant; Anticancer